Electronic Metal‐Support Interaction‐Modified Structures and Catalytic Activity of CeOx Overlayers in CeOx/Ag Inverse Catalysts. Issue 70 (7th November 2019) - Ren, Muqing; Qian, Kun; Huang, Weixin
Abstract: Electronic metal‐support interactions (EMSIs) of oxide‐supported metal catalysts strongly modifies the electronic structures of the supported metal nanoparticles. The strong influence of EMSIs on the electronic structures of oxide overlayers on metal nanoparticles employing cerium oxides/Ag inverse catalysts is reported herein. Ce2 O3 overlayers were observed to exclusively form on Ag nanocrystals at low cerium loadings and be resistant to oxidation treatments up to 250 °C, whereas CeO2 overlayers gradually developed as the cerium loading increased. Ag cubes enclosed by {001} facets with a smaller work function exert a stronger EMSI effect on the CeO x overlayers than Ag cubes enclosed by {111} facets. Only the CeO2 overlayers with a fully developed bulk CeO2 electronic structure significantly promote the catalytic activity of Ag nanocrystals in CO oxidation, whereas cerium oxide overlayers with other electronic structures do not. These results successfully extend the concept of EMSIs from oxide‐supported metal catalysts to metal‐supported oxide catalysts. Abstract : Electronic metal‐support interactions (EMSIs) occur in CeO x /Ag inverse catalysts via charge transfer from Ag to CeO x . Ag cubes enclosed by {001} facets with a smaller work function exert a stronger EMSI effect than Ag cubes enclosed by {111} facets. The EMSIs strongly affect the electronic structures and catalytic activity of the CeO x overlayers on the Ag nanocrystals in CeO x /Ag inverse catalysts.